Coleoptera diversity and abundance in Golcuk Natural Park, in Isparta, Turkey - Japoshvili, G.; Kaya, M.; Aslan, B.; Karaca, I. (ENTOMOLOGIA HELLENICA, 2009)
Coleoptera diversity was investigated at Golcuk Natural Park, Isparta, Turkey. Thirty four families of Coleoptera were recorded during the survey. Coleopterans were most abundant in a site close to an old apple orchard where 33% of all sampled individuals were found. Less frequently recorded families were found in a site close to the main entrance and picnic area. Coleopteran families were found to be unequally partitioned in all six microhabitats. The highest similarity index (0.85) was found between sites close to the Park entrance and close to the old apple orchard. Distribution of the abundance of coleopteran families was significantly different between all studied habitats. The study revealed that the site close to the old apple orchard and sites with xerophilic natural plants provide special micro-habitats for Coleopteran fauna.